The cave - Waring, Rob.; Jamall, Maurice (Boston : Thomson ELT, 2006)
Faye, John, and their friends are on their boat. They find a secret cave full of interesting things. Later, the water comes up and they cannot get out. How do they get out of the cave?
1 2
Keywords: Readers; Caves -- Juvenile literature; Caving -- Juvenile literature